2015
DOI: 10.1021/acs.orglett.5b01686
|View full text |Cite
|
Sign up to set email alerts
|

Activating a Cryptic Ansamycin Biosynthetic Gene Cluster To Produce Three New Naphthalenic Octaketide Ansamycins with n-Pentyl and n-Butyl Side Chains

Abstract: Genome mining is a rational approach to discovering new natural products. The genome sequence analysis of Streptomyces sp. LZ35 revealed the presence of a putative ansamycin gene cluster (nam). Constitutive overexpression of the pathway-specific transcriptional regulatory gene nam1 successfully activated the nam gene cluster, and three novel naphthalenic octaketide ansamycins were discovered with unprecedented n-pentylmalonyl-CoA or n-butylmalonyl-CoA extender units. This study represents the first example of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…S13 †). Interpretation of the NMR data (Tables 1 and 2) revealed that 1 had similar structure as that of neoansamycin B, 15 except for the substitute of a hexyl at C-20 instead of an amyl side chain, and which was further conrmed by the 1 H-1 H COSY and HMBC correlations (ESI Table S1 and Fig. S1 †).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…S13 †). Interpretation of the NMR data (Tables 1 and 2) revealed that 1 had similar structure as that of neoansamycin B, 15 except for the substitute of a hexyl at C-20 instead of an amyl side chain, and which was further conrmed by the 1 H-1 H COSY and HMBC correlations (ESI Table S1 and Fig. S1 †).…”
Section: Resultsmentioning
confidence: 92%
“…13,14 Recently, Streptomyces sp. LZ35 was activated to produce novel naphthalenic ansamycins (neoansamycins A-C) by constitutive overexpression of a LuxR family transcriptional regulatory gene, 15 and further ten new benzenic ansamycins (5,10-seco-neoansamycins A-J) were obtained by disrupting the nam7 gene in the SR201nam1OE strain. 16 The intriguing structure diversity of the neoansamycins A-C and 5,10-seco-neoansamycins A-J encouraged us to search for more new congeners of neoansamycins.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Silence genes activation. Li et al [21] activated a putative ansamycin gene cluster (nam) of Streptomyces sp. LZ35, and three new naphthalenic octaketide ansamycins (3-5 Fig.…”
Section: Redesign Of Metabolic Flowmentioning
confidence: 99%
“…XZQH13 were discovered when the large ATP-binding regulators of the LuxR family (LAL) transcriptional activator genes, vemR and astG1 were constitutively expressed, respectively [12,13]. Moreover, two novel chattamycins were discovered when overexpressing an atypical response regulator (ARR) family regulator gene, chaI [14]; and overexpression of a LuxR family activator gene nam1 led to production of three new naphthalenic octaketide ansamycins [15]. For the jadomycin and gaudimycin biosynthetic pathways, however, no significant effects were observed when ARR family activator genes were overexpressed [16 • ].…”
Section: Activation Of Silent Bgcs In Native Hostsmentioning
confidence: 99%